Maliyeden müdevver 18155 numaralı ruus defteri (transkripsiyon ve değerlendirme) - Çolak, Onur (My University, 2024)
Osmanlı tarihi araştırmalarında günümüz teknoloji ve imkanlarına rağmen tarihçilerimizin yaşadığı en büyük sıkıntı özellikle Divan-ı Hümayun kalemlerine bağlı defterler ve muamele görmüş belgelere rahatça ulaşıp faydalanamamaları, araştırmalarda ana kaynaklara gerektiği kadar başvuramamalarıdır. Bu durum şüphesiz ki Osmanlı arşiv kaynaklarının yeterince transkribe edilip değerlendirilmemiş olmasından kaynaklanmaktadır. İşte biz de üzerine çalışmakta olduğumuz 18155 Numaralı Ruus Defteri’nin transkripsiyonunu ve değerlendirmesini yaparak bu eksikliği bir nebze olsun gidermeyi ve tarih araştırmaları için bir başvuru kaynağı daha meydana getirmeyi amaçlamaktayız. Elimizdeki defter beklenenin aksine ARSK.d veya KK. tasniflerine değil Maliyeden Müdevver tasnifine alınmış olup Eylül 1601-Kasım 1603 tarihleri arasında yaşanan tayin, azil, tevcih, terakki ve mansıpları gün esasına göre kaydetmektedir ki karanlıkta kalmış olan XVII. yüzyıl başına ait tayin ve aziller için bu kaynak paha biçilmezdir. Çalışmamızda adı geçen defterin transkripsiyonu yapılmış, büyük tevcihâtdan küçük tevcihâta doğru olmak üzere tasnif edilmiş ve daha kolay anlaşılabilmesi için tablolaştırılmıştır. Ayrıca her bölümde kayıtların değerlendirmesi yapılmıştır.

Despite today's technology and opportunities in Ottoman history research, the biggest problem experienced by our historians is that they cannot easily access and benefit from the notebooks and processed documents attached to the Imperial Council pens, and that they cannot give the necessary space to the main sources in research. This situation is undoubtedly due to the fact that Ottoman archive sources have not been adequately transcribed and evaluated. By transcribing and translating the Ruus Notebook No. 18155, which we are working on, we aim to eliminate this deficiency to some extent and create another reference source for historical research. Contrary to expectations, the notebook we have is ARSK.d or KK. It was discovered not in the classification but in the MAD. classification. It records day by day the appointments, dismissals, promotions, advancements and appointments that took place between September 1602 and November 1603. In this way, the 17th century documents, which was left in the dark will be brighten. This source has been an invaluable resource for the appointments and dismissals made at the Early XII.yy Ottoman Empire. In our study, the mentioned notebook was transcribed in accordance with the original without alteration or destruction, classified as central and provincial, and tabulated for easier understanding. In addition, a brief evaluation of the records has been made in each chapter, so that readers who are not familiar with the subject can understand the records.
Keywords: Azil; Civil Service; Devlet Hizmeti; Dismissal; MAD; Maliyeden Müdevver; Osmanlı İmparartorluğu; Osmanlı İmparatorluğu; Ottoman Empire; Progress; Repentance; Ruus; Tayin; Terakki Ottoman Empire